Sistem Informasi Pariwisata Kabupaten Tabanan Berbasis Website - Mitha Amartya Rosalinda; Ni Wayan Ayu Suartini (Universitas Ivet, 2021)
The island of Bali has many beautiful places and there are still many people who don't know about them. One of them is located in Tabanan Regency, where there are still many who do not know the tourism. Therefore, the Website-Based Tabanan Regency Tourism Information System is created where this website is used as a tool in the delivery of information on tourism areas in Tabanan Regency to people who want to know the tourism areas in Tabanan. If the community will become more familiar with tourist attractions in Tabanan Regency, the food of the surrounding residents will also increase. Keywords: Tabanan Regency Tourism Information System Based Website